Effects of Integrated Nutrient Management on the Growth Performance of Beetroot (Beta vulgaris L.) under Acidic Soil Conditions in Smallholder Farmer Fields - Mohammad Samiul Ahsan Talucder; Akram Hossain; Rafia Islam Tisha; Md Abu Sayed Robi; Lathuenu Marma; Most. Papia Sultana; Ahasan, Ahasan Ullah Khan (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
This research examines the impact of integrated nutrient management on the growth, yield, sugar content, and betalain concentration of beetroot cultivated in acidic soil (pH 4-5) within the farmer's field at Khadimnagar, Sylhet, Bangladesh. A randomized complete block design (RCBD) was used to assess six fertilizer treatments combining varying rates of Urea, MoP, TSP, and vermicompost. This study aimed to evaluate how integrated nutrient management affects the growth, yield, and quality of beetroot in acidic soil conditions. The results indicated significant effects of the treatments on the majority of parameters. Key findings showed that moderate nutrient application (T3: 300-150-300 kg/ha N-P-K + 3500 kg/ha vermicompost) produced the highest yield (26.75 t/ha), with significant improvements in root weight, length, diameter, and betalain content. In contrast, excessive fertilization (T5) led to reduced yield and quality, while no fertilization (T0) resulted in the poorest performance. The highest sugar content (Brix%) was observed in T2 at 7.775%, suggesting a positive effect of moderate nutrient application. The results indicate that a combination of N-P-K at 300-150-300 kg/ha with vermicompost at 3500 kg/ha is optimal for improving beetroot quality and productivity in slightly acidic soils. The control group (T0) exhibited the lowest performance across all measured parameters. The study highlights the importance of balanced nutrient management in acidic soils. The data suggests that higher nutrient doses (T3 and T5) lead to significant improvements in beetroot growth, quality, and yield, with T3 generally showing superior performance across key metrics. Further field trials are recommended to validate these findings across broader agroecological contexts.